Crystallization and preliminary X‐ray crystallographic analysis of the amylomaltase from Corynebacterium glutamicum. Issue 9 (30th August 2013) - Srisimarat, Wiraya; Murakami, Shuichiro; Pongsawasdi, Piamsook; Krusong, Kuakarun
<x xml:space="preserve">Abstract</x> Amylomaltase (AM; EC 2.4.1.25) belongs to the 4‐α‐glucanotransferase group of the α‐amylase family. The enzyme can produce cycloamylose or large‐ring cyclodextrin through intramolecular transglycosylation or cyclization reactions of α‐1, 4‐glucan. Amylomaltase from the mesophilic bacterium Corynebacterium glutamicum (CgAM) contains extra residues at the N‐terminus for which the three‐dimensional structure is not yet known. In this study, CgAM was overexpressed and purified to homogeneity using DEAE FF and Phenyl FF columns. The purified CgAM was crystallized by the vapour‐diffusion method. Preliminary X‐ray data showed that the CgAM crystal diffracted to 1.7 Å resolution and belonged to space group P212121, with unit‐cell parameters a = 73.28, b = 82.61, c = 118.64 Å. To obtain the initial phases, crystals of selenomethionyl‐substituted amylomaltase were produced, and multiple‐wavelength anomalous dispersion phasing and structure refinement are now in progress.